Utilizing a mindfulness application in the nursing classroom. Issue 1 (2nd January 2023) - Flatekval, Anne Marie
ABSTRACT: Mindfulness is a practice that is advantageous for decreasing anxiety and stress (McVeigh, 2021). It is very beneficial to use with students. Nursing students experience much stress and anxiety due to the academic workload and expectations to perform in the classroom and clinical setting (Manocchi, 2017 ). It is important for students to be able to manage stress and anxiety so that they can be successful in the nursing program. When first year nursing students indicated they were experiencing stress and anxiety and it was negatively impacting their academic performance, brief mindfulness sessions were introduced at the beginning of each class. Student feedback has been very positive for using a mindfulness application. This demonstrates that mindfulness applications have a positive impact on the reduction of stress and anxiety which is beneficial in the classroom, clinical setting, and everyday practice.